"Pra nós, todo o amor do mundo”: formação de identidade e consumo musical dos fãs da banda Los Hermanos - Neves, André Luiz (2018)
Music is used by individuals in various contexts, and may even help them to consolidate their sense of identity, through the formation of their musical preferences and the occasions of consumption in which they can express their personality. The objective in this work is characterizing and describing the identity dimensions of the fans Los Hermanosband and their influence on the consumption and the extension of the self. The theoretical references focused on the evolution and characteristics of the music market, as well as issues related to cultural identity, symbolic consumption, and the construction of identity and extension of the self through the music consumption. We used the qualitative approach and, as a technical procedure, the case study. In order to explore and know the research field, in a first moment, materials were analyzed such as the band discourse in interviews granted to third parties, the lyrics of the songs, the information and products offered by the official site, the band page in social networks, as well as what is said by fans in posts on social networks. Subsequently, we sought to analyze the fans‟ relation with the Los Hermanosband and consumption patterns of products and services related to it. For this, interviews were conducted by virtual means, which allowed the contact with people dispersed geographically. As a sample delimitation, individuals aged from 25 to 45 years old were interviewed, who in their youth, had contact with the band, developing and maintaining their appreciation for it until nowadays. The main features of fans‟ identity were identified, which are the hermetism in the conviviality, determination in the achievement of goals and reflection on everyday situations, often performed in a lyric and romanticized way. Interviewees have an intimate relation with the music, usually linked by eclecticism. The first contacts with the work of Los Hermanosband were generally by influence of closest people, through television programs or specialized music stores. A peculiar characteristic found in these fans is their greater fixation by the songs themselves, and not so much by the artists of the group. They characterize the band by the diversity of their songs, as well as the use of different rhythms and not very conventional instruments to bands of the same genre. The main impact that Los Hermanosband songs generate in the fans is the incentive to reflection, and they look for in them a support to what they are experiencing, or to the attitudes that they take towards themselves and the other people. The biggest consumption of products and services by fans is represented by CDs, DVDs, vinyl records, T-shirts and, especially, attending the band's concerts. Even, the nostalgia generated by the band dissolution arouses the fans‟ admiration, reinforcing the fan/artist relation, the identity projects and the consumption practices of products and services associated to the group.